Can exposure to acidic beverages following the application of fluoride varnish cause changes in the amount of fluoride release? an in vitro study - Bhaswati Chakraborty; Arathi Rao; Reshma K Chandra; Ramya Shenoy; Baranya S Suprabha (Wolters Kluwer Medknow Publications, 2017)
Introduction: Fluoride varnishes are found to be effective in the prevention of early childhood caries. Postvarnish application, the instructions provided by the manufacturer seem to be inadequate because they do not mention the type of beverages which can be consumed after the specified time, considering the widespread consumption of soft acidic drinks in children. Aim: The study was conducted to evaluate the amount of fluoride released from fluoride varnishes − Fluorprotector and Bifluorid in artificial saliva and acidic conditions. Materials and Methods: Polymethyl methacrylate blocks were painted with fluoride varnish and placed into artificial saliva for 30 min. Blocks were then placed in either 1% citric acid or 0.3% citric acid solutions for 30 min with the solutions being replaced every 5 min. The solution was analyzed for fluoride content. Results and Conclusion: The statistical tests applied were repeated measures of analysis of variance and student's t-test. The level of significance was kept at P < 0.05. Significant difference in fluoride release was noted in different acidic mediums. Fluoride release from fluoride varnishes varied considerably and also depended on the dissolution medium.